Renal Excretion of Contrast on CT Myelography: A Specific Marker of CSF Leak - Behbahani, S.; Raseman, J.; Orlowski, H.; Sharma, A.; Eldaya, R. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: The purpose of this study was to evaluate the sensitivity and specificity of renal/ureteric opacification on postmyelographic CT as a sign of CSF leak.MATERIALS AND METHODS: We performed a retrospective review of postmyelographic CT scans from 49 consecutive patients seen between January 2008 and August 2018 with imaging and/or clinical findings related to intracranial hypotension. Each scan was evaluated by both a neuroradiology fellow and a board-certified neuroradiologist for the presence of contrast in the renal excretory system. A similar assessment was also performed on 90 consecutive control subjects who underwent CT myelography for alternative indications.RESULTS: Among the 49 patients with suspected CSF leak, 21 (43%) had an overt CSF leak on postmyelographic CT (group 1) and 28 (57%) did not (group 2). Overall, renal contrast was identified in 7/49 patients (14.3%): 5 (24%) patients in group 1, and 2 (7%) patients in group 2. Renal contrast was not seen in any of the 90 controls on postmyelographic CT.CONCLUSIONS: Renal contrast was exclusively seen in patients with a clinically or radiographically suspected CSF leak. Given its 100% specificity, identification of this finding should prompt a second look for subtle myelographic contrast extravasation or an underlying CSF-venous fistula. Our results suggest that this sign may be considered an additional diagnostic criterion for CSF leak in the absence of an identifiable leak.CTMCT myelogramCVFCSF-venous fistulaICHintracranial hypotension